Changes induced in the representation of auditory space in the superior colliculus by rearing ferrets with binocular eyelid suture. - King, A; Carlile, S (1993)
There have been conflicting reports concerning the importance of visual experience in the development of auditory localization mechanisms. We have examined the representation of auditory space in the superior colliculus of adult ferrets that were visually deprived by binocular eyelid suture from postnatal days 25-28, prior to natural eye opening, until the time of recording. This procedure attenuated the transmission of light by a factor of a least 20-25 and blurred the image so that, as long as the eyelids were still fused, the responses of visual units in the superficial layers of the superior colliculus were labile and very poorly tuned. After the eyelids were opened, the representation of the visual field in these layers appeared to be normal. Acoustically responsive units were, as usual, almost exclusively restricted to the deeper layers of the superior colliculus. However, unlike normal animals, where responses occurring only at stimulus onset predominate, most of these units exhibited sustained or multi-peaked discharge patterns. The degree of spatial tuning of individual units recorded from the normal and deprived groups of animals was not significantly different in either azimuth or elevation. Normally orientated maps of both sound azimuth and elevation were also found in the visually deprived ferrets. However, abnormalities were present in the topography and precision of these representations and consequently in their alignment with the overlying visual map. In particular, an increase was observed in the proportion of auditory units with spatially ambiguous receptive fields, in which the maximum response occurred at two distinct locations. These results indicate that patterned visual experience is not required for establishing at least a crude map of auditory space in the superior colliculus, but suggest that it may play a role in refining this representation during development.